Pre-Extension Demonstration of Improved Bread Wheat Varieties with Their Production Packages in High land Area of Eastern Amhara Region, Ethiopia - Abere Haile; Negussie Siyum; Mekonnen Assefa; Mesfin Bahta (Universitas Panji Sakti, 2021)
The study was basically focused on demonstration of bread wheat technologies for wider demand-driven technology diffusion in major wheat growing area in high land of eastern Amhara. The objectives were in order to evaluate and demonstrate improved bread wheat variety with their production package to the farming community and assess farmers and extension workers reaction towards improved bread wheat technology. The activity was conducted in main season 2019/2020 at Jama and Meket districts. The fact that wheat production and productivity in the region as well as in the particular study area low because farmers are using low yielding, disease and pest resistant local varieties. The improved bread wheat variety was demonstrated along with the local variety at 12 farmers' fields. Yield data, economic data, farmers’ perception and preferences were collected throughout the demonstration stages and data were analyzed by using ANOVA, partial budget analysis and preference ranking. The results of ANOVA showed that yield and yield related parameters statistically significant at the probability level of 0.01% and 0.05% among treatments. The highest mean yield was recorded from